2005
DOI: 10.1007/s11120-005-0790-2
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme co-localization in pea leaf chloroplasts: glyceraldehyde-3-P dehydrogenase, triose-P isomerase, aldolase and sedoheptulose bisphosphatase

Abstract: Nearest neighbor analysis of immunocytolocalization experiments indicates that the enzymes glyceraldehyde-3-P dehydrogenase, triose-P isomerase and aldolase are located close to one another in the pea leaf chloroplast stroma, and that aldolase is located close to sedoheptulose bisphosphatase. Direct transfer of the triose phosphates between glyceraldehyde-3-P dehydrogenase and triose-P isomerase, and from glyceraldehyde-3-P dehydrogenase and triose-P isomerase to aldolase, is then a possibility, as is direct t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 46 publications
0
10
1
Order By: Relevance
“…PGK1 also plays important roles in the glycolytic pathway, and PGK1 and GAPDH are potentially co-regulated [56]. In our data, however, their potential co-regulation was not significant.…”
Section: Discussioncontrasting
confidence: 78%
“…PGK1 also plays important roles in the glycolytic pathway, and PGK1 and GAPDH are potentially co-regulated [56]. In our data, however, their potential co-regulation was not significant.…”
Section: Discussioncontrasting
confidence: 78%
“…1-3). Both subunits are also colocalized with the Calvin cycle enzymes P-glycerate kinase (Anderson et al, 2003), triose-P isomerase, and aldolase (Anderson et al, 2005), but only the B subunit appears to be colocalized with transketolase (Anderson et al, 2006). Both subunits are co-localized with thioredoxin m, but only the A subunit is co-localized with thioredoxin f (Anderson and Carol, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Anderson and Carol (2004) found that labeling for RCA occurred in the chloroplast of pea plants. Hong et al (2005) also demonstrated that RCA protein was distributed in the chloroplast of bundle sheath and mesophyll cells of the C 4 plant Amaranthus tricolor.…”
Section: Discussionmentioning
confidence: 99%